Пристрій для аналізу та пошуку оптимальних параметрів каналів радіозв’язку з ППРЧ - Шостко, І. С.; Цибульников, Д. І. (ХНУРЕ, 2021)
In the scientific work proposed description of the method of increasing the noise immunity and explanatory scheme of the proposed improvement method is given. The search for the optimal parameters of building a communication system also held.
Keywords: Пристрій для аналізу та пошуку; Радіозв'язок з ППРЧ